PENGARUH FASILITATOR PENDAMPING DAN KELEMBAGAAN TERHADAP TINGKAT KINERJA KEUANGAN DENGAN PENGAWASAN PEMERINTAH DAERAH SEBAGAI VARIABEL MEDIASI - Ayumilawarty, Ayumilawarty; Mas'ud, Arifuddin; husin, Husin (JPEP (Jurnal Progres Ekonomi Pembangunan), 2019)
This study aims to find out and analyze the influence of facilitator and institutional facilitators on the level of financial performance with the supervision of local government as a mediating variable. This study is an expo facto research using the survey method. The population in this study was 64 respondents from Kelurahan Unit Management in Kendari City. The sample of this study is the entire study population which amounted to 64 financial management units.The results of the study show that the facilitator has a positive and significant effect on financial performance. The facilitator has a negative and insignificant effect on the supervision of the local government, the institution has a positive and not significant effect on financial performance, the institution has a positive and significant effect on the supervision of the local government and supervision of the regional government positive and significant effect on financial performance. Regional government oversight is not able to act as a mediating variable on the relationship of facilitating facilitators in improving financial performance and supervision of local government capable of acting as a mediating variable on the relationship of facilitating facilitators in improving financial performance.